Health design thinking : creating products and services for better health - Ku, Bon, ....-; Lupton, Ellen, 1963- (Cambridge : The MIT Press, 2020)
"Health Design Thinking is a step-by-step guide to the creative process, written for health care providers, educators, patients, and designers who seek to create better experiences and improved health outcomes for individuals and communities. Health design challenges exist all around us, from how to reduce medical errors to reimagining hospital waiting areas or planning an outpatient clinic journey. As health care systems around the world struggle to improve care and control costs, leaders in the field of medicine are embracing the methods of "design thinking." While countless organizations have adopted the principles of design thinking, there exists no practice-based guide addressing the special overlap of health care and the creative process. Health Design Thinking is co-authored by Dr. Bon Ku, a practicing physician and the Assistant Dean for Health and Design at the Sidney Kimmel Medical College of Thomas Jefferson University, and Ellen Lupton, a senior curator at Cooper Hewitt, Smithsonian Design Museum and an established author whose books on design processes are used by educators worldwide. The co-authors propose to publish the book with Cooper Hewitt, one of the world's leading platforms for design and a thought leader on design thinking"--